International exchange students KMITL-UiTM: fostering interdisciplinary excellence / Amirul Hakim Zulkifli, Hasiful Fata Talhah and Shahrool Rezza Salim - Zulkifli, Amirul Hakim; Talhah, Hasiful Fata; Salim, Shahrool Rezza (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
We are delighted to introduce one of our collaborative programs between King Mongkut’s Institute of Technology Ladkrabang (KMITL), Thailand And UiTM Cawangan Pulau Pinang (UiTMCPP) that was held on 25th May until 23rd June 2023. It was designed to enhance interdisciplinary learning, research, and innovation. This innovative partnership has brought together the strengths and expertise of both universities in creating a dynamic academic environment that benefits not only students and institutions but communities of both countries as well. The perks of the program include: > Promoting interdisciplinary collaboration between students and faculty, > Facilitating joint research projects and academic initiatives. > Enhancing international exposure and cultural exchange opportunities. > Strengthening academic programs through shared resources and expertise.